Research on Wireless Power Transfer Efficiency in Rail Transit - LE Wentao; LYU Zhuo; LIU Huadong (Kongzhi Yu Xinxi Jishu)
Aiming at the problems of rail transit wireless power transfer (WPT) technology such as low efficiency and high radiation, this paper proposed a multi-coil coupling LCL-S circuit topology and its soft switching technology which could effectively improve system efficiency. At the same time, in order to reduce the flux leakage of the coupling mechanism, an optimized coil structure as figure-8 was proposed. Experimental results of a 150 kW dual-coil coupling principle prototype show that the proposed circuit topology has good constant voltage characteristics: the average efficiency of the high-frequency inverter is 98.9% as in the soft switching state, flux leakage of the figure-8 coil is about 42% less than that of the conventional one, and the average transmission efficiency of the system is greater than 90.2%.